Analysis of long‐term observations of NOx and CO in megacities and application to constraining emissions inventories. Issue 18 (22nd September 2016) - Hassler, Birgit; McDonald, Brian C.; Frost, Gregory J.; Borbon, Agnes; Carslaw, David C.; Civerolo, Kevin; Granier, Claire; Monks, Paul S.; Monks, Sarah; Parrish, David D.; Pollack, Ilana B.; Rosenlof, Karen H.; et al.
Abstract: Long‐term atmospheric NOx /CO enhancement ratios in megacities provide evaluations of emission inventories. A fuel‐based emission inventory approach that diverges from conventional bottom‐up inventory methods explains 1970–2015 trends in NOx /CO enhancement ratios in Los Angeles. Combining this comparison with similar measurements in other U.S. cities demonstrates that motor vehicle emissions controls were largely responsible for U.S. urban NOx /CO trends in the past half century. Differing NOx /CO enhancement ratio trends in U.S. and European cities over the past 25 years highlights alternative strategies for mitigating transportation emissions, reflecting Europe's increased use of light‐duty diesel vehicles and correspondingly slower decreases in NOx emissions compared to the U.S. A global inventory widely used by global chemistry models fails to capture these long‐term trends and regional differences in U.S. and Europe megacity NOx /CO enhancement ratios, possibly contributing to these models' inability to accurately reproduce observed long‐term changes in tropospheric ozone. Key Points: Measured NOx /CO enhancement ratio trends are compared to inventory emissions ratio trends in megacities Chemistry‐climate modeling inventory fails to capture NOx /CO emission ratio trends and regional differences Observations demonstrate divergent paths in motor vehicle emission control strategies in the U.S. versus Europe